Program Pengembangan Minat Kewirausahaan Mahasiswa - Lilik Sri Hariani; Endah Andayani; Nurul Ain (Jurnal Pemberdayaan Masyarakat, 2018)
The objective of developing entrepreneurship program to produce new entrepre-neurs. The methods in this activity were training, workshops, and observations. The results of implementation program among others, a very good commitment of tenants have been carried out all activities, the amount of attendance of tenants for each activity were 100%, their activeness in each activity were good and the average activity in 78 %, the successful of program is good and the program success rate in 75 %. We hope all of the activities implementation of developing entrepreneurship program increase the tenants interesting in entrepreneurship. It is recommended for the team to assist tenant activities until they can be independent entrepreneurs.